FACE-Q Craniofacial Module: Part 1 validation of CLEFT-Q scales for use in children and young adults with facial conditions. Issue 9 (September 2021) - Klassen, Anne F; Rae, Charlene; Wong Riff, Karen WY; Bulstrode, Neil; Denadai, Rafael; Goldstein, Jesse; Hol, Marinka LF; Murray, Dylan J; Bracken, Shirley; Courtemanche, Douglas J; O'Hara, Justine; Butler, Daniel; et al.
Summary: Background: The CLEFT-Q includes 12 independently functioning scales that measure appearance (face, nose, nostrils, teeth, lips, jaws), health-related quality of life (psychological, social, school, speech distress), and speech function, and an eating/drinking checklist. Previous qualitative research revealed that the CLEFT-Q has content validity in noncleft craniofacial conditions. This study aimed to examine the psychometric performance of the CLEFT-Q in an international sample of patients with a broad range of facial conditions. Methods: Data were collected between October 2016 and December 2019 from 2132 patients aged 8 to 29 years with noncleft facial conditions. Rasch measurement theory (RMT) analysis was used to examine Differential Item Function (DIF) by comparing the original CLEFT-Q sample and the new FACE-Q craniofacial sample. Reliability and validity of the scales in a combined cleft and craniofacial sample (n=4743) were examined. Results: DIF was found for 23 CLEFT-Q items when the datasets for the two samples were compared. When items with DIF were split by sample, correlations between the original and split person locations showed that DIF had negligible impact on scale scoring (correlations ≥0.995). In the combined sample, RMT analysis led to the retention of original content for ten CLEFT-Q scales, modification of the Teeth scale, and the addition of an Eating/Drinking scale. Data obtained fit with the Rasch model for 11 scales (exception School, p=0.04). Person Separation Index and Cronbach alpha values met the criteria. Conclusion: The scales described in this study can be used to measure outcomes in children and young adults with cleft and noncleft craniofacial conditions.